Students’ Learning Motivation in primary School IPAS: The Role of a Deep Learning Approach - Avika Nourma Sella; Endah Marwanti; Dyan Indah Purnama Sari (Journal of Education and Teaching Learning, 2026)
This study aims to examine the influence of the deep learning approach on students’ learning motivation in Integrated Science and Social Studies (IPAS) at the elementary school level. The study employed a quantitative method with an ex post facto design involving all Grade III students at SD Negeri Bakalan, Bantul, Yogyakarta. Data were collected through questionnaires and classroom observations and analyzed using simple linear regression. The findings indicate that the deep learning approach has a positive and statistically significant influence on students’ learning motivation, as shown by a regression coefficient of 0.165 and a significance value of 0.032 (< 0.05). The t-test result (2.278 > 1.713) also confirms a significant relationship between the variables. These findings suggest that meaningful, reflective, and student-centered learning activities contribute to stronger motivational responses among students. The study provides empirical evidence regarding the importance of deep learning in supporting motivation within elementary IPAS learning.